SISTEM PENDUKUNG KEPUTUSAN PADA SELEKSI PENERIMAAN SISWA SEKOLAH MENENGAH KEJURUAN - Dea Trisna Ananda; Astria Hijriani; Febi Eka Febriansyah (Jurnal Komputasi, 2016)
Every educational institution of Vocational High School periodically carries out the admission of new students. With the existence of Decision Support System is expected to assist schools in selecting new students. There are various methods in constructing a DSS and one of them is the method of AHP. AHP is one of DSS method that can handle the multi criteria selection. By using the result of DSS with AHP method as sample data and find the biggest criteria factor in a selection. The result of this study indicates that AHP method can be implemented in information system of new students admission and it can help to make decisions in the placement of departments based on the ability of students and the selected department.Keywords: Analytical Hierarchy Process (AHP), Decision Support System (DSS)